Low‐temperature‐grown gallium arsenide photoconductors with subpicosecond carrier lifetime and photoresponse reaching 25 mA/W under 1550 nm CW excitation. Issue 17 (1st August 2020) - Tannoury, C.; Billet, M.; Coinon, C.; Lampin, J‐F.; Peytavit, E.
Abstract : The authors show in this Letter that photoconductors based on GaAs grown at low temperatures can exhibit photoresponses as high as 25 mA/W under continuous‐wave 1550‐nm‐wavelength illumination. It is achieved by using an optical Fabry–Pérot cavity in order to improve the external quantum efficiency and by decreasing the post‐growth annealing temperature down‐to 450°C.